2021
DOI: 10.1371/journal.pone.0257491
|View full text |Cite
|
Sign up to set email alerts
|

Human milk-based fortifier is associated with less alteration of milk fat globule size than cow milk-based fortifier

Abstract: We aimed to evaluate if human milk-based fortifier (HMBF) affects human milk fat globule (MFG) size less than cow milk-based fortifier (CMBF), which may impact overall infant feeding tolerance. Measurements of donated human milk were performed before fortification as well as at 1 hour, 24 hours, and 48 hours after fortification with CMBF or HMBF. MFG size in each sample of fortified milk was measured by laser light scattering. MFG size in the fortified milks increased gradually over time. At 24 and 48 hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There are two types of multicomponent fortifiers, bovine or human milk-based. Yoshida et al [45] found that human milk-based fortifier might enhance feeding tolerance of very preterm infants because of its less alteration of milk fat globule. However, this research did not evaluate the difference in clinical trial.…”
Section: Individualized Fortificationmentioning
confidence: 99%
“…There are two types of multicomponent fortifiers, bovine or human milk-based. Yoshida et al [45] found that human milk-based fortifier might enhance feeding tolerance of very preterm infants because of its less alteration of milk fat globule. However, this research did not evaluate the difference in clinical trial.…”
Section: Individualized Fortificationmentioning
confidence: 99%